Makers of modern India - Guha, Ramachandra (Cambridge, Mass. : Belknap, 2011)
Includes a short biographical introduction to each person, followed by excerpts from their writings.
Includes bibliographical references and index.
Keywords: Political culture -- India -- History -- 18th century -- Sources